(untitled) (Annals of Medical Research, 2021)
Aim: Allergic reactions that develop after venom can be serious and fatal. The only treatment that can prevent these serious reactions is venom immunotherapy. Studies on venom immunotherapy in paediatric patients are limited. Aim of this study to evaluate the demographic data and laboratory results of paediatric patients who have received venom immunotherapy. Materials and Methods: The study included 45 patients who have received subcutaneous venom immunotherapy in Department of Paediatric Allergy and Immunology. Results: Thirty-three of the patients (73.3 %) were boys and 12 (26.7 %) were girls, the median age was 14 years (min.: 6, and max. 18). Apis mellifera venom was given to 24 (53.3 %) of 45 patients, and Guapes species venom immunotherapy was given to 21 (46.7 %) patients. While 15 (33.3 %) patients who received immunotherapy were living in Malatya, 30 patients were living in various provinces of the Eastern Anatolia region. While wide local reaction developed in 15 (33.3%) of the patients, systemic reaction developed in 3 (6.7 %) patients during venom immunotherapy. Apis mellifera prick test median diameter was determined as 4 mm and median of Apis specific Ig E value was determined as 6 kU/L. Guapes species prick test median diameter was determined as 4 mm and median of Guapes specific Ig E value was determined as 4 kU/L. Conclusion: Immunotherapy with Apis venom was more than Guapes venom in current study. Large local reaction was observed in 1/3 of the patients during immunotherapy. Therefore, attention should be paid in terms of systemic allergic reactions and large local reactions during immunotherapy. All necessary precautions should be taken during the immunotherapy.